Perception of Importance and Strategies of Medical Documentation among Physicians in Emergency Departments in Jordan - Qazaqi, Salah Moh'd (Journal of medical and pharmaceutical sciences, 2022)
This study purposed to identify the perception of importance and strategies of medical documentation among physicians in emergency department in Jordanian government hospitals. The Methodology; A descriptive design was adopted and data were collected from 79 physicians working in emergency department in government hospitals in Jordan. A self-reported questionnaire consists of two parts: importance of documentation (9 items) and strategies of documentation (7 items) was utilized. The findings showed that the mean score for documentation was (3.69), which indicates that physicians have a good degree of documentation. Also, the mean for the dimension of importance of documentation was (3.53), and the mean for the dimension of documentation was (3.86), which indicates that physicians have good scores. Recommendations: The results indicate the importance of medical documentation for all physicians in the emergency department, which indicates its importance and the need to take care of this aspect in these departments. Therefore, it is necessary to develop different plans to use different methods of documentation in the emergency department and to develop policies regarding supporting emergency departments and increasing the number of physicians in these departments in government hospitals.